MANAJEMEN KONFLIK DALAM PERNIKAHAN ENDOGAMI DAN EKSOGAMI: ANALISIS PERSPEKTIF ISLAM DAN PSIKOLOGI KELUARGA - Nadhira Mahmudah; Alexsander Bahar (LPPM STAI Muhammadiyah Probolinggo, 2026)
The number of divorces in Indonesia due to arguments and disputes has been increasing every year, caused by the lack of awareness among couples in understanding household conflict management before marriage. North Bontang ranks first in terms of the number of Muslim residents, migrants, and divorces in Bontang. The purpose of this study is to compare endogamous and exogamous marriage conflict management that survives amid high divorce rates in North Bontang and analyze its compatibility with Islamic law. This study uses a qualitative approach with a descriptive-comparative analysis method through interviews via Google Forms and literature studies. The results of the study show that there is no significant difference between the patterns of managing conflicts in endogamous and exogamous marriages in North Bontang, even though exogamous marriages have a different cultural background. The results of the analysis also prove the compatibility of the conflict management patterns of both marriages with Islamic law principles, which include responses to conflict, conflict resolution, and sustainable preventive strategies. Both of these show that Islamic values can be a universal alternative in domestic conflict management, regardless of cultural differences. This study contributes to the development of Islamic value-based domestic conflict management that can be internalized by married couples in dealing with domestic dynamics.